Analiza systemów zdobień w graduale Kraków, AiBKKK, Ms 45 .......... 191 - Jakubek-Raczkowska, Monika; Raczkowski, Juliusz (Graduał wawelski (Kraków, AiBKKK, Ms 45): Studium przypadku, 2025)
ANALYSIS OF THE SYSTEM OF DECORATION IN A 15TH-CENTURY GRADUAL, KRAKOW, AIBKKK, MS 45The richly decorated Gradual Ms 45 stands out in the rich and stylistically coherent legacy of 15th-century Krakow book painting. It is an example of the so-called composite manuscripts – the texts it contains were written at different times and by different hands, which explains the striking variety of its decorations of uneven artistic levels. In addition to the main part of the manuscript, written by one hand and decorated according to a single concept, there are many other scribes and at least five systems of decoration, found on additional leaves 1–34. The article discusses them from the point of view of form, relation to the text and technique of execution, with particular emphasis on the main part, the most artistically valuable, executed in the early period of Krakow book painting in the 1st quarter of the 15th century. These illuminations were introduced to art history studies by Barbara Miodońska, who, on the basis of an analysis of the figural and floral ornamentation, correctly pointed out that this part of the codex was created in the Kraków scriptorium, which worked under Bohemian influence, and linked it to the Hutter Bible and several other manuscripts decorated in the same style. The article presents a study of the production process and a comparative analysis of the style of the entire decoration in terms of its relationship to the Prague illuminations of the turn of the 14th century and against the background of the Hutter Bible workshop. The much more modest, rather standard decoration of the first parts of the text, written in the 15th century by several hands, is discussed separately.